Implementation of national screening guidelines for gestational diabetes: A national survey of maternity units in England. (December 2018) - Bell, Ruth; Hayes, Louise; Pasecinic, Nicoleta; Heslehurst, Nicola
Highlights: 39% of NHS Trusts are not compliant with all NICE GDM risk-factor screening criteria. Main non-compliance was for previous GDM, BMI ≥ 30 and ethnicity risk-factors. Barriers to BMI ≥ 30 compliance were capacity, resource and funding for screening. 41% used diagnostic thresholds for GDM which differed from NICE recommendations. Resources are required to fully implement and sustain risk-factor screening. Abstract: Aims: To describe national implementation of gestational diabetes (GDM) risk-factor based screening guidelines, and barriers to implementation relating to maternal body mass index (BMI). Methods: National online survey of NHS Trusts offering maternity services in England. A questionnaire was emailed to clinical staff involved in care of pregnant women assessing compliance with NICE guidelines for risk-factor based screening, BMI thresholds for offering OGTT and barriers to offering OGTT to women with BMI ≥ 30 kg/m 2 . Results: Health professionals from 113 (84%) of NHS Trusts in England responded to the survey. Most Trusts (81%) offered OGTT at 26–28 weeks gestation to women with selected risk factors for GDM. However, almost 40% of Trusts were not fully compliant with NICE screening criteria for all risk factors, mainly due to not offering OGTT to women with previous GDM (25% of Trusts), BMI ≥ 30 kg/m 2 or ethnic minority groups (22% of Trusts). The main barriers to compliance with the BMI threshold were lack of capacity, resource and funding given the high prevalence of maternal obesity. Forty one percent of Trusts used diagnostic thresholds for GDM which differed from NICE recommendations. Conclusions: Additional resources are required for NHS Trusts to fully implement and sustain risk-factor screening, especially for women with previous GDM, BMI ≥ 30 kg/m 2 and ethnic minority groups.